2016
DOI: 10.1007/s11019-016-9688-3
|View full text |Cite
|
Sign up to set email alerts
|

The utility of standardized advance directives: the general practitioners’ perspective

Abstract: Advance directives (AD) are written documents that give patients the opportunity to communicate their preferences regarding treatments they do or do not want to receive in case they become unable to make decisions. Commonly used pre-printed forms have different formats. Some offer space for patients to (a) appoint a surrogate decision maker, and/or (b) to determine future medical treatments and/or (c) give a statement of personal values. So far it is unknown which forms GPs preferably use and why they decide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
1
8
0
6
Order By: Relevance
“…Doctors in this study reported validity concerns to be a key barrier to ACD adherence, in accordance with past Australian and international research findings 15 18 20 24. Doubts about validity, including currency of decisions, were particularly prominent where participants disagreed with the treatment decision specified in the ACD.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Doctors in this study reported validity concerns to be a key barrier to ACD adherence, in accordance with past Australian and international research findings 15 18 20 24. Doubts about validity, including currency of decisions, were particularly prominent where participants disagreed with the treatment decision specified in the ACD.…”
Section: Discussionsupporting
confidence: 86%
“…In responding to the scenario, only 32% of doctors reported that they would adhere to the ACD in accordance with the law. Studies have identified a number of barriers to ACD adherence, including family opposition,14–16 lack of clinical relevance15 17–20 and concerns about the validity of ACDs 15 18 20…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found individuals with lived experience of caring for someone else at end of life, or experience with ACP had increased uptake of ACP,47 58 and this also included GPs with personal experience of ACP 31. Two studies reported the process of discussion and reflection of values over multiple visits as enabling ACP to be most effective,14 34 supported by similar findings from others 43 57 64 65…”
Section: Resultsmentioning
confidence: 74%
“…System level barriers to ACP were commonly considered in the available literature. Common system level concerns included, for example, the suitability of ACP templates45 57; or uncertainty about the efficacy of one information kit versus another 53. Lack of consensus about what information was required in a written ACP including the relative importance of value statements, contributed to a lack of clarity 45.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation